A Study on Causes of Azoospermia in Urology Clinic of Yasuj University of Medical Sciences - SMR Rabani; A Moosavizadeh (Armaghane Danesh Bimonthly Journal, 2006)
ABSTRACT: Introduction & Objective: Azoospermia means no sperm in semen. It may be due to hormonal imbalance, any disorder in production of sperm, or might be due to obstruction in sperm pathway from testis till ejaculatory ducts. This study was performed to determine the causes of azoospermia in infertile male, referred to Yasuj clinic of urology.